THE USE OF COOPERATIVE SCRIPT METHOD TOWARD STUDENTS’ LISTENING SKILL - Darlin, Darlin; Sale, Firdaus; Agustina, Sitti (Universitas Halu Oleo, 2020)
This study was conducted to examine whether there is or not any significant effect of cooperative script method on students’ listening skill at class XI IPA II of SMA Negeri 1 Parigi. This research was conducted in pre-experimental research design. The population of this study was the grade eleventh science program (XI IPA) students of SMA Negeri 1 Parigi which consists of two classes with the total of the students were 48 students, while the sample of this study was the grade eleventh science program (XI IPA II) which consists of 23 students. In this study, the researcher taught the students by using cooperative script method. The method was applied in the treatment for four meetings. The students were given listening test for every meeting during treatment. The data were analyzed by using SPSS 16.0 version by using (descriptive analysis and inferential statistics). Descriptive analysis was used to describe standard deviation, mean score, maximum scores and minimum scores, while the inferential statistic was used to examine the hypothesis (paired sample t-test) which was calculated through SPSS 16, 0. Based on the finding, the mean score of students listening achievement.